A STUDY ON THE EUROPEAN FOX HUNTING: FROM THE PERSPECTIVE OF FABRIC THEORY - REFERRING TO THE EVOLUTION OF CIVILIZATION - Wang, Linlin; Chen, Liquan (Universitas Pendidikan Indonesia, 2024)
Fabric theory, also known as